Determination and analysis of the complete mitochondrial genome sequence of Wugangtong grey goose. (3rd March 2016) - Lin, Qian; Jiang, Gui-Tao; Cao, Rong; Yun, Long; Li, Guo-Jun; Dai, Qiu-Zhong; Zhang, Shi-Rui; Hou, De-Xing; He, Xi
Abstract: Mitochondrial DNA plays an important role in living organisms. In this study, the complete mitochondrial genome sequence of the Wugangtong grey goose was reported in Human Province first, which was determined through PCR-based method. The total length of the mitogenome is 16, 740 bp. It contains the typical structure, including 2 ribosomal RNA genes, 22 transfer RNA genes, 13 protein-coding genes and 1 non-coding control region (D-loop region) as that of most other vertebrates. The overall composition of the mitogenome was estimated to be 30.22% for A, 22.67% for T, 32.05% for C and 15.07% for G. All the protein initiation codons are ATG, except for COX1, COX2 and ND5 are GTG, ND6 is CTA. The complete mitochondrial genome sequence of the Wugangtong grey goose will provides an important data set for the study in genetic mechanism of goose in Hunan province.